Emancipatory Potential in Feminist Security Studies. Issue 4 (5th August 2013) - Basu, Soumita
<x xml:space="preserve">Abstract</x> Forum: The State of Feminist Security Studies: Continuing the Conversation. This forum comprises seven pieces conceived in response to the recent Politics & Gender Critical Perspectives section that featured contributions from Carol Cohn, Valerie Hudson, Jennifer Lobasz, Laura Sjoberg, Ann Tickner, Annick Wibben, and Lauren Wilcox (P&G 2011, Vol. 7, Issue 4). Throughout, we refer to this collection as "the CP section."